Utilizing ultrasound findings of a single indicator joint to assess non-systemic juvenile idiopathic arthritis - Yung-Hsien Huang; Ya-Chiao Hu; Chun-Hua Liao; Bor-Luen Chiang; Cheng-Hsun Lu; Ko-Jen Li; Yao-Hsu Yang (BMC, 2021)
Abstract Background Musculoskeletal ultrasound (MSUS) has been used worldwide in adult patients with rheumatoid arthritis (RA) but is beginning to play an increasing role in patients with juvenile idiopathic arthritis (JIA). The aim of this study was to investigate the application of MSUS findings of a single indicator joint in JIA to assess the disease activity and classify disease subtype. Methods Thirty-five non-systemic JIA patients with a total of 62 visits were retrospectively recruited in this study. Among the involved joints, the joint with highest value of grey-scale (GS) plus power Doppler (PD) (=GSPD) was selected as the indicator joint at each visit. The correlations between each MSUS parameter (GS, PD, GSPD) of indicator joints and the Physician Global Assessment (PGA) score, the Childhood Health Assessment Questionnaire-disability index (CHAQ-DI), and laboratory data were analyzed. The ultrasound features in different subtypes of JIA were also compared. Results PD was weakly correlated with the PGA score (rho = 0.323, p = 0.010), while both GS and GSPD were moderately correlated with the PGA score (rho = 0.405, p = 0.001; rho = 0.434, p = 0.000). On the other hand, GS, PD, and GSPD were weakly correlated with CHAQ-DI. Although erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) had a weak correlation with PGA, they were not statistically correlated with GS, PD, or GSPD. The proportions of effusion, synovial hypertrophy, and enthesopathy in three different subtypes, showed significant differences (Fisher's exact test, p = 0.037; p = 0.004; p = 0.019). Enthesopathy was only seen in joints of enthesitis-related arthritis (ERA), but not in joints of polyarthritis and oligoarthritis. Conclusions MSUS is an acceptable non-invasive tool for the patients with JIA, particularly for those with non-systemic JIA, that might assist disease classification, and whose parameters of the indicator joints may potentially contribute to the evaluation of disease activity.